2014
DOI: 10.1111/wusa.12136
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Bodies and Labor Rights: Workers in China's Automotive Industry

Abstract: This article focuses on the serious occupational health and safety (OHS) injuries affecting the workers of one of China's most important industries-automotive assembly-and particularly the musculoskeletal disorders (MSDs) that are common in the industry. The data are drawn from a 2011 survey of 1,100 autoworkers conducted at twelve assembly plants in seven Chinese cities. By correlating injury rates with age, speed of the assembly line, length of work hours, mental pressure, availability of floaters to replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Located within the debate on the impact of lean demands on employee well‐being, we address these questions in this paper, using survey data from a Chinese lean manufacturer of transportation equipment. Existing studies in China, which is the world's largest contributor to manufacturing output, show evidence of a negative lean implementation‐to‐well‐being relationship (e.g., Chan, Chen, Xie, Wei, & Walker, ; Zhang, ). In order to enhance worker outcomes in China, we need studies of the types of job resources that may counterbalance the lean job demands being faced by the workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Located within the debate on the impact of lean demands on employee well‐being, we address these questions in this paper, using survey data from a Chinese lean manufacturer of transportation equipment. Existing studies in China, which is the world's largest contributor to manufacturing output, show evidence of a negative lean implementation‐to‐well‐being relationship (e.g., Chan, Chen, Xie, Wei, & Walker, ; Zhang, ). In order to enhance worker outcomes in China, we need studies of the types of job resources that may counterbalance the lean job demands being faced by the workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a survey of 1100 autoworkers (whose average age was 24 years) from 12 lean assembly plants, Chan et al. () found that musculoskeletal disorders were common due to inappropriate setup of workstations, the speedup of the assembly line and long working hours. As a result, 48.3% of the sampled workers reported that, under their current work conditions, they did not envisage being able to keep working until the age of 40, a frightening statistic in terms of their well‐being and one that suggests a high cost to firms in terms of employee turnover.…”
Section: Job Resources Job Demands and Flm Well‐being Under Lean Promentioning
confidence: 99%
“…Other scholars provide mixed structure‐agent studies and hence more nuanced views (Chan ; Chan et al ; Friedman ; Friedman and Lee ; Gallagher ; Lee ; Lau ). Their prospects for the future of Chinese labor movement have likewise waxed and waned over the past two decades.…”
Section: Insurgency or Stagnancy: An Overview Of Chinese Labor Movementmentioning
confidence: 99%